Pengaruh Teknik Bernyanyi dan Permainan Kartu Bergambar Terhadap Sikap dan Perilaku Gizi Pada Anak Taman Kanak-Kanak - Virmando, Eri; Anantanyu, Sapja; Kusnandar, Kusnandar (Media Kesehatan Masyarakat Indonesia, 2018)
Nutrition education in kindergarten children is an effort to increase awareness of healthy living behavior in consumption of fruits and vegetables through Communication, Information, and Education (CIE). This study aims to analyze the effect of nutritional education through the technique of singing and picture card games to the attitudes and nutritional behavior of kindergarten children. The design in this study was quasi-experimental, with pre-post test design with control group design. The subjects of this study were 68 students from 4 kindergarten schools in Tempilang Subdistrict, this study was conducted in January - March 2018. Nutrition education used was a technique of singing, card game, and joint intervention. The results show that there are differences in nutritional attitudes and behaviors in nutritional education. The combined intervention has the highest score on the attitudes and nutritional behavior of 7.38 ± 0.98 and 49.06 is significantly different from other intervention media. There was a change of good nutrition that increased after intervention (97,1%) from before intervention (95,6%) and change of good nutrition behavior that increased after intervention (45,6%) before intervention (79,4%). Nutrition education through joint intervention provides a change in the improvement of nutritional attitudes and behaviors in child kindergartens.